2011
DOI: 10.1029/2011gl046807
|View full text |Cite
|
Sign up to set email alerts
|

Depth dependence of rupture velocity in deep earthquakes

Abstract: [1] Explaining deep seismicity is a long-standing challenge in earth science. Between 300 and 700 km depth, earthquakes are scarce except between ∼530 and ∼600 km, where the majority of events occur. By imaging the seismic rupture process for a set of recent deep earthquakes using the back projection of teleseismic P-waves, we found that the rupture velocities are less than 60% of the shear wave velocity except in the depth range of 530 to 610 km. We propose that large fracture surface energy (G c ) values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…Several studies 5,18 support this hypothesis, although they tend to indicate that the average rupture velocity for deep earthquakes is about 0.6V S , somewhat slower than the 0.7-0.8V S empirically determined for shallow earthquakes 16,19 . Given this small difference, the limited number of deep earthquakes for which rupture velocity can be accurately determined, and a known tendency of underestimating the rupture velocity of deep earthquakes 20 , no systematic trend of the rupture velocity is considered in most of this study.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies 5,18 support this hypothesis, although they tend to indicate that the average rupture velocity for deep earthquakes is about 0.6V S , somewhat slower than the 0.7-0.8V S empirically determined for shallow earthquakes 16,19 . Given this small difference, the limited number of deep earthquakes for which rupture velocity can be accurately determined, and a known tendency of underestimating the rupture velocity of deep earthquakes 20 , no systematic trend of the rupture velocity is considered in most of this study.…”
mentioning
confidence: 84%
“…We provide in Fig. 4 5,18 by assuming that the average ratio between rupture velocity and shear velocity decreases from 0.8 for shallow earthquakes to 0.6 for 600-km-deep earthquakes, a modest increase of the strain drop with depth is present. As the strain drop variation depends on the cube of the ratio, strain drop should change by a factor of 2.4-3 (and stress drop by a factor of 14-18) when moving from the surface to the deepest seismogenic zones.…”
Section: Scardec Stfsmentioning
confidence: 99%
“…7.0) below 400 km. Nor was a clear relationship between rupture velocity and f seen by Suzuki and Yagi (2011). The dependence indicates the sensitivity of the deep earthquake rupture process to slab temperature and was interpreted by Wiens (2001) and Tibi et al (2003a) as support for the thermal shear instability mechanism.…”
Section: Thermal Parametermentioning
confidence: 96%
“…The distribution of $100 estimates of rupture velocities from various studies is shown in Figure 8 after Frohlich (2006a). For most intermediate and deep earthquakes, rupture velocities range from 0.4b to 0.9b (e.g., Suzuki and Yagi, 2011and Tibi et al, 2002, 2003aWarren et al, 2007), but they are notably slower (0.2-0.4b) for very large deep South American events -1963Peru-Bolivia, 1970Colombia, and 1994Bolivia (Beck et al, 1995Estabrook, 1999;Furumoto, 1977). For most intermediate and deep earthquakes, rupture velocities range from 0.4b to 0.9b (e.g., Suzuki and Yagi, 2011and Tibi et al, 2002, 2003aWarren et al, 2007), but they are notably slower (0.2-0.4b) for very large deep South American events -1963Peru-Bolivia, 1970Colombia, and 1994Bolivia (Beck et al, 1995Estabrook, 1999;Furumoto, 1977).…”
Section: Spatial Pattern Of Rupture Rupture Velocity and Stress Dropmentioning
confidence: 99%
See 1 more Smart Citation